2014
DOI: 10.1103/physrevb.89.195308
|View full text |Cite
|
Sign up to set email alerts
|

Electron-electron interaction mediated indirect coupling of electron and magnetic ion or nuclear spins in self-assembled quantum dots

Abstract: We show here the existence of the indirect coupling of electron and magnetic or nuclear ion spins in self-assembled quantum dots mediated by electron-electron interactions. With a single localized spin placed in the center of the dot, only the spins of electrons occupying the zero angular momentum states couple directly to the localized spin. We show that when the electron-electron interactions are included, the electrons occupying finite angular momentum orbitals interact with the localized spin. This effecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The controlled incorporation of magnetic impurities in a semiconductor provides a means to manipulate magnetic and electronic interactions, one of the exciting challenges in modern condensed matter systems 1 . In particular, the interactions between magnetic ions and a host material constrained to low dimensionality provide an additional degree of freedom in tailoring physical properties and a route to the discovery of phenomena of fundamental and technological interest 2 3 4 5 6 .…”
mentioning
confidence: 99%
“…The controlled incorporation of magnetic impurities in a semiconductor provides a means to manipulate magnetic and electronic interactions, one of the exciting challenges in modern condensed matter systems 1 . In particular, the interactions between magnetic ions and a host material constrained to low dimensionality provide an additional degree of freedom in tailoring physical properties and a route to the discovery of phenomena of fundamental and technological interest 2 3 4 5 6 .…”
mentioning
confidence: 99%
“…This provides the emission theory for magnetically doped charged QDs. As a consequence, we observed that electron-electron interaction mediates indirect exchange interaction between electron and Mn and predict how to detect electron spin on half filled electronic shells [53,55].…”
Section: Chapter 1 Introductionmentioning
confidence: 86%
“…Here we present a detailed description of the CI method. We use it to describe the electronic and optical properties of CdTe quantum dots doped with an single magnetic impurity [53,55,58,62,78]. To describe the QD electronic states, we model it as a two-dimensional harmonic oscillator.…”
Section: Configuration Interaction Methodsmentioning
confidence: 99%
See 2 more Smart Citations